Child poverty and child benefits in the European Union - Herwig Immervoll; Holly Sutherland; Klaas de Vos (University of Essex, Institute for Social and Economic Research (ISER), 2000)
Using evidence from the European Community Household Panel we find that family benefits vary in their importance to household incomes and in the prevention of child poverty across Europe. In one group of countries family benefits appear to have a significant effect on the protection of children from financial poverty. The UK and the Netherlands are both members of this group, and we use the microsimulation model EUROMOD to examine the extent to which differences in child benefits explain the very different level of child poverty in the two countries. We also explore the effect of “swapping” child benefit systems between the two countries and find that there is some scope for improvements in looking beyond national borders. We conclude that the poverty reduction properties of universal child benefits may be improved without resorting to means-testing or compromising the other functions of these benefits. This analysis illustrates that comparative microsimulations can be extremely informative, and provides a flavour of the potential of EUROMOD to offer valuable pointers for the direction of social policies.
Keywords: C81; D31; I38; 330; Child poverty; European Union; Child benefits; Microsimulation; Armut; Kinder; Familienleistungsausgleich; Simulation; EU-Staaten